Death Receptor 5 Displayed on Extracellular Vesicles Decreases TRAIL Sensitivity of Colon Cancer Cells - Setroikromo, Rita; Zhang, Baojie; Reis, Carlos R.; Mistry, Rima H.; Quax, Wim J. (Frontiers in Cell and Developmental Biology, 2020)
TRAIL is considered to be a promising anti-tumour drug due to its selective pro-apoptotic properties on tumour cells. However, the clinical application of TRAIL is till now limited due to the resistance of several cancer cells, which can occur at various levels in the TRAIL signalling pathway. The role of decoy receptors that can side-track TRAIL, thereby preventing the formation of an activated death receptor, has been extensively studied. In this study we have focused on extracellular vesicles (EVs) that are known to play a role in cell-to-cell communication and that can be released by donor cells into the medium transferring their components to recipient cells. TRAIL-induced apoptotic signalling is triggered upon the binding of two death receptors, DR4 and DR5. Here, we found that DR5 but not DR4 is present in the conditioned medium (CM)-derived from various cancer cells. Moreover, we observed that DR5 was exposed on EVs and can act as “decoy receptor” for binding to TRAIL. This results in a strongly reduced number of apoptotic cells upon treatment with DR5-specific TRAIL variant DHER in CM. This reduction happened with EVs containing either the long or short isoform of DR5. Taken together, we demonstrated that colon rectal tumour cells can secrete DR5-coated EVs and this can cause TRAIL resistance. This is to our knowledge a novel finding and provides new insights into understanding TRAIL sensitivity.